3х+2х=17-27
5х=-10
х=-10:5
х=-2
6х-7х=3.5*(-1)+4
-1х=0.5
х=-0.5
-2,2X=-5,5;
2,2X=5,5;
X=5,5/2,2
X= 5/2;
X=2,5.
Объяснение:
1) 3х + 2х = 17 + (-27)
5х = 17 - 27
5х = -10
х = -2
2) 6х - 7х = 3,5 × (-1) + 4
-х = -3,5 + 4
-х = 0,5
х = -0,5
3) 1,3х - 3,5х = 11 × (-0,5)
-2,2х = -5,5
х = 2,5
3х+2х=17-27
5х=-10
х=-10:5
х=-2
6х-7х=3.5*(-1)+4
-1х=0.5
х=-0.5
-2,2X=-5,5;
2,2X=5,5;
X=5,5/2,2
X= 5/2;
X=2,5.
Объяснение:
1) 3х + 2х = 17 + (-27)
5х = 17 - 27
5х = -10
х = -2
2) 6х - 7х = 3,5 × (-1) + 4
-х = -3,5 + 4
-х = 0,5
х = -0,5
3) 1,3х - 3,5х = 11 × (-0,5)
-2,2х = -5,5
х = 2,5